The Urgency of the Regulation of Certification as an Attempt to Optimize the Human Resources in Developing Indonesia’s Sharia Insurance - lastuti abubakar Gani; Tri Handayani (Tazkia Islamic Finance and Business Review, 2015)
Objectives - The development of Islamic insurance in Indonesia contributed to economic growth in 2014. The principle of mutual cooperation and tabarru contract is a characteristic of Islamic insurance. The Opportunity to increase the role of Islamic insurance as an economic entity is done by utilizing various aspects of human resource readiness. Human Resource are required to have a comprehensive understanding of Islamic insurance in order to create compliance with Islamic principles for product and services offered.It can provide legal protection against the Takaful participants. Issues to be examined is how the readiness of the relevant regulatory certification and how Regulatory model certification appropriate human resources in order to develop Islamic insurance in Indonesia.              Methods -The method used is a normative juridical that through the efforts of an inventory of rules and descriptive analytical. To obtain the appropriate regulatory models, a legal comparison method is employed.Results - Based on the research results, the regulation of certification is required and should include the human resources, starting from a selling agent to the management as a decision maker. This regulation will push the entire human resources involved in the Islamic insurance industry to has the capacity and capability in providing services to the public, and to ensure and guarantee that the services offered comply with Islamic principles. Association of Islamic Insurance Indonesia was initiated concerning certification provisions, but has not been followed by a strong regulations readiness as a legal basis.Conclusion -Therefore we need a comprehensive regulation and it must be issued by Indonesian Financial Services Authority.